ANALISIS BRAND IMAGE, CITA RASA DAN KUALITASPRODUK TERHADAP KEPUASAN PELANGGAN KOPIJANJI JIWA JAKARTA(STUDI PADA MAHASISWA DI JAKARTA SELATAN) - Muhammad Farhan Nurrachim (2022)
This type of research conducted by researchers is a quantitative study that aims to determine Brand Image Analysis, Taste and Product Quality on Customer Satisfaction. This study used a sample of 100 respondents from a student population in South Jakarta who had made at least two purchases at Kopi Janji Jiwa. The sampling technique uses non-probability sampling using purposive sampling. The data collection carried out in this study used an online questionnaire using the Google Form which was then distributed via the LINE, Whatsaap, Instagram and Chat applications personally to respondents who met the criteria. This study uses the PLS (Partial Least Square) analysis technique with the SmartPLS 4.0 application. The results obtained from this study are: (1) Brand Image variable has a positive and significant effect on customer satisfaction with an original sample value of 0.253. (2) Taste variable has a positive and significant effect on customer satisfaction with an original sample value of 0.363. (3) Product Quality variable has a positive and significant effect on customer satisfaction with an original sample value of 0.366.